Evaluation and Management of Pulmonary Hypertension in Kidney Transplant Candidates and Recipients: Concepts and Controversies. Issue 1 (January 2017) - Lentine, Krista L.; Villines, Todd C.; Axelrod, David; Kaviratne, Summanther; Weir, Matthew R.; Costa, Salvatore P.
Abstract : Abstract: Although cardiac evaluation before kidney transplantation commonly focuses on coronary artery disease, a comprehensive pretransplant cardiac evaluation must consider other prognostically important cardiac conditions including functional and structural heart disease. Pulmonary hypertension (PH) is increasingly recognized among patients with kidney failure and may be driven by left heart failure, high cardiac output from arteriovenous fistula, hypoxic lung diseases, and metabolic derangements associated with renal disease. In this article, we examine several key concepts and controversies relevant to optimizing the assessment and management of PH in kidney transplant candidates and recipients. First, categorizing PH according to underlying pathophysiologies, hemodynamic characteristics, and treatment responses as currently defined by the World Health Organization can be challenging in this population, but should be pursued to direct appropriate management. Second, echocardiographic PH (based on variable definitions) has been reported in 13% to 50% of selected pretransplant cohorts, but use of more precise diagnostic methods is needed to better define epidemiology and underlying etiologies. Third, although measures of PH have been associated with adverse patient and graft outcomes after kidney transplantation, pilot data suggest that PH may improve with successful transplantation. Fourth, recent advances in PH treatment in the general population focus on World Health Organization group 1 pulmonary arterial hypertension, and the efficacy of management strategies for any PH type in patients with renal failure is largely unproven. Broader prospective data, including attention to the impact of transplantation, are needed to advance understanding of the frequency, causes, and optimal management of PH in kidney transplant candidates and recipients. Abstract : An examination of the concepts and controversies relevant to the management of pulmonary hypertension in kidney transplant candidates and recipients, including diagnostic challenges, echocardiographic definition, optimal management, new therapies, treatment response, and association with kidney transplant outcomes.